Evaluating regulation within an artificial financial system: A framework and its application to the liquidity coverage ratio regulation - Jesper Riedler; Frank Brueckbauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We develop a general model of the financial system that allows for the evaluation of bank regulation. Our framework comprises the agents and institutions that have proved crucial in the propagation of the subprime mortgage shock in the U.S. into a global financial crisis: Commercial banks and investment banks, which can also be interpreted as shadow banks, interact on wholesale debt markets. Beside a market for short term interbank loans and long term bank bonds, other funding sources include insured customer deposits, uninsured investor deposits and repos. While credit to the real sector is the principal asset of commercial banks, investment banks specialize in trading securities, which may differ according to risk, maturity and liquidity. As a first application of the model we implement the liquidity coverage ratio (LCR) regulation and analyze its impact on bank balance sheets, interest rates, the transmission of monetary policy and the stability of bank lending in the face of shocks. We find that the LCR regulation reduces the supply of loans to the real sector, increases the maturity and interest rate of long term wholesale debt, and strongly diminishes the role of the overnight interbank market as a funding source. Our simulations suggest that the transmission of changes to short term monetary policy rates is severely impaired when the LCR regulation is binding. Furthermore, we find that a strong confidence shock can lead to a protracted credit crunch under the liquidity regulation.
urn:nbn:de:bsz:180-madoc-433600
Keywords: 330; financial system; agent-based model; liquidity coverage ratio